The role of overlayered nitride electro-materials for N2 reduction to ammonia - Abghoui, Younes; Iqbal, Atef; Skúlason, Egill (Frontiers in Catalysis, 2023)
Following our previous report on N2 reduction reaction (NRR) on the surface of nitrides, we investigated the influence of incorporation of titanium nitride as a stable and inactive-NRR material into the structure of DFT-predicted NRR-active surfaces of chromium, vanadium, niobium, and zirconium nitrides. The outcome of our density functional theory (DFT) based analyses suggests that combination of titanium nitride with vanadium nitride can enhance the potential-determining step of the reaction with up to 20% compared to pure vanadium nitride while maintaining similar number of proton-electron transfer steps for formation of two ammonia molecules. The influence of titanium nitride on chromium nitride is expected to be more pronounced as rate-determining step associated with nitrogen adsorption on the vacancy and regeneration of the catalyst improves by around 90% compared to the pure chromium nitride. This effect on niobium and zirconium nitride is, however, negative as the potential-determining step becomes larger for the case of niobium nitride, and the reaction pathway changes from nitrogen reduction to hydrogen evolution for the case of zirconium nitride. These results not only encourage experimentalists to explore these combinatorial structures further in experiments, but it also opens up the avenue for considering the alloys and dopants of these nitrides via both DFT modelling and experiments.